2010
DOI: 10.4021/jocmr2010.05.288w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Approaches for Management of Child and Adolescent Obesity

Abstract: Overweight and obesity among children and adolescents continue to be a global public health epidemic. Current national data on childhood and adolescent obesity show alarming statistics of overweight and obese children and adolescents. This epidemic runs across various continents and affects various ethnic populations. The current weight management practices involve dietary modification, behavioral change therapies involving exercise, pharmacological therapy and surgical intervention. The purpose of this curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
(29 reference statements)
0
15
0
9
Order By: Relevance
“…37 In addition, to our knowledge, no study has shown this weight loss to be sustained after stopping the medication. 38,39 Combined behavior, diet, and pharmacotherapy programs in adolescents have demonstrated minimal longitudinal efficacy as well; in 3 recent trials, [40][41][42] BMI decreased by an average of 1.82, and only 71% of patients completed therapy after 1 year.…”
Section: Rationale For Surgical Treatment Of Obesity In Adolescentsmentioning
confidence: 99%
“…37 In addition, to our knowledge, no study has shown this weight loss to be sustained after stopping the medication. 38,39 Combined behavior, diet, and pharmacotherapy programs in adolescents have demonstrated minimal longitudinal efficacy as well; in 3 recent trials, [40][41][42] BMI decreased by an average of 1.82, and only 71% of patients completed therapy after 1 year.…”
Section: Rationale For Surgical Treatment Of Obesity In Adolescentsmentioning
confidence: 99%
“…2,3 For this reason, pharmacologic support using metformin has been implemented in addition to dietary hygiene measures, which are not sufficient to re-establish normoglycemic metabolic markers in a number of cases. [3][4][5] Metformin is an antihyperglycemic drug that maintains decreased blood glucose levels and sensitizes peripheral tissues to insulin's action without causing hypoglycemia. [4][5][6] Excepting the United States and Canada, there is no commercial presentation with customized doses that can be easily administered to children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss with the use of medications is limited (typically Ͻ 3 kg more than control subjects) and maintaining the weight loss and long-term effects of pharmacotherapy for obesity in adolescents is largely unknown (Kanekar & Sharma, 2010;Rogovik et al, 2010). Insurance often does not pay for weight loss medication, and cost often prohibits its use.…”
Section: Consmentioning
confidence: 99%
“…Moreover, since the removal of sibutramine (Meridia) from the market in 2010 due to its association with heart disease, the only currently available, long-term pharmacotherapy agent for obesity in adolescents is orlistat (Kanekar & Sharma, 2010;Sarwer & Dilks, 2011). Orlistat (Xenical) is a lipase inhibitor and functions to reduce fat malabsorption by blocking about 30% of dietary fat with the typical 120-mg dose three times a day for adolescents (Greydanus et al, 2011;Rogovik et al, 2010).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%